Critical extinction exponent for a doubly degenerate non-divergent parabolic equation with a gradient source. Issue 12 (10th September 2018) - Liu, Dengming; Mu, Chunlai
Abstract: We concern with the extinction phenomenon of a non-divergent parabolic equation with a nonlinear gradient source. The critical extinction exponent of the solution is obtained.